2005
DOI: 10.1097/01.smj.0000184800.83171.f7
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Emergence of Methicillin Resistance in Community-acquired Staphylococcus aureus Infections in Denver

Abstract: A single strain of methicillin-resistant S aureus is responsible for the increase in skin infections in outpatients without traditional risk factors for infection with an antibiotic-resistant strain. In areas with high rates of methicillin-resistant S aureus outpatient infections, we recommend non-beta-lactam antibiotics for initial treatment of skin and soft tissue infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…14,18 However, during the last several years, CA-MRSA infections have been noted in patients without these risk factors. [15][16][17]19,20,24 Consistent with these reports, our study found no significant difference between MRSA-positive and MRSA-negative patients with respect to CA-MRSA risk factors, bringing into question the usefulness of the risk factor profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,18 However, during the last several years, CA-MRSA infections have been noted in patients without these risk factors. [15][16][17]19,20,24 Consistent with these reports, our study found no significant difference between MRSA-positive and MRSA-negative patients with respect to CA-MRSA risk factors, bringing into question the usefulness of the risk factor profile.…”
Section: Discussionmentioning
confidence: 99%
“…14-17 These CA-MRSA infections have become increasingly common, and now affect patients who lack previously identified MRSA risk factors. 14,[18][19][20] Some authors have noted that CA-MRSA possesses a number of virulence factors that have been associated with more aggressive disease. 21,22 In addition, CA-MRSA often possesses 'different antibiotic susceptibilities than hospital-acquired MRSA.…”
mentioning
confidence: 99%
“…However, the proportion caused by CA-MRSA strains (defined by a specific antibiotic susceptibility pattern) doubled from 24% to 49% (732). In Denver, CO, at a city-owned hospital and its affiliated clinics, the number of community-acquired (i.e., a culture obtained from an ED or clinic or within 48 h after a hospital admission) S. aureus SSTIs did not increase overall, but the percentage caused by MRSA increased from 6% in the first quarter of 2002 to 45% in the second quarter of 2004 (P Ͻ 0.001) (173). Similarly, in the Calgary Health Region of Canada, as MRSA became a more common cause of S. aureus bacteremia in 2000 to 2006, the total incidence of S. aureus bacteremia did not rise (512).…”
Section: Ca-mrsa: An Epidemic and Its Originsmentioning
confidence: 99%
“…1 More recently, Clancy et al 2 described an increase in CA-MRSA strains in Denver, Colorado, from 6% to 45% during a 2-year period. The patients infected with these strains did not have the typical risk factors for MRSA.…”
mentioning
confidence: 99%
“…9 Since then, multiple reports have been published. 2,[7][8][9] Four deaths due to CA-MRSA occurred in Minnesota during a 2-year period. 8 In one Texas…”
mentioning
confidence: 99%